The Beginnings of Formal Semantics: The Historical Context of Arnim von Stechow’s Contributions - Partee, Barbara H. (Proceedings of Sinn und Bedeutung, 2019)
The paper surveys the development of formal semantics and its ties to analytic philosophy and generative grammar.